Identifying a core set of medical informatics serials : an analysis using the MEDLINE database - SITTIG, D. F (Bulletin of the Medical Library Association, 1996)
A study was undertaken to test the hypothesis that a core set of medical informatics serials could be identified by using standard bibliometric techniques. All journal articles indexed by the National Library of Medicine between 1990 and 1994 were included. Articles were identified by using the "MEDICAL INFORMATICS" Medical Subject Heading (MeSH) term. Each serial title containing articles was then ranked according to (1) the total number of medical informatics journal articles indexed and (2) the percentage of medical informatics journal articles indexed. Twenty-eight serials had more than 100 articles indexed under the "MEDICAL INFORMATICS" MeSH term. Thirty serials had more than 40% of their articles indexed under the "MEDICAL INFORMATICS" MESH term. A "core" set of fourteen serials had 100 or more medical informatics articles indexed, including more than 70% of all articles they published. The methodology described provides librarians with another tool to use in the difficult task of journal selection. The set of "core" serials identified provides librarians with a ranked list of serials, based on which a medical informatics collection can be developed.